High performance coach education: A symbolic interactionist perspective - Kolic, P. (Manchester Metropolitan University, 2018)
This thesis focuses on the experiences of those individuals involved in the formation, consumption, management, and delivery of the United Kingdom Coaching Certificate Coach Level 4 (UKCC CL4) award. An ethnographically inspired fieldwork engagement of 18 months followed cohorts of UKCC CL4 coaches from British Canoeing and British Judo as they undertook this education journey. This research comes at a time when UK sporting agencies have invested considerable resources into elite coach education and have established novel relationships with Higher Education institutions (HEi) to assist in the delivery of such programmes. Despite this investment, there is a scarcity of empirically informed studies detailing the processes undertaken. Little is understood in terms of what aspirations, thoughts, fears, and beliefs the participants have had, which includes an understanding of the problems and contradictions inherent in the UKCC CL4 award itself. Over 50 interviews with coaches, course tutors, Governing Body (GB) staff and sports organisations` personnel were conducted; the data gleaned from these were analysed using the theories inherent in the writings of traditional symbolic interactionists, such as Blumer (e.g. Blumer, 1946; 1969), Cooley (e.g. Cooley, 1907; 1910; 1918), Mead (Mead, 1934), and Strauss (e.g. Strauss, 1959; 1978). Findings indicate that there are three main areas of significance: that the individuals responsible for the management of the relationship between the sport GB and the HEi partner are of central importance; that over the period of the UKCC CL4 award, well thought out and constructed links between the theoretical aspects covered in the delivery and practice of coaches resulted in stronger levels of attainment; and, that a number of the coaches completing the UKCC CL4 programme developed an ongoing desire for further academic educational experience having established a strong commitment to personal development. The significance of this work is that it provides empirically informed guidelines for the development of similar coach education programmes at home in the UK and abroad by privileging the views and experiences of those participants directly involved in high performance coach education.